Aggregation in carbon dots: Special Issue: Emerging Investigators. Issue 6 (21st November 2022) - Ru, Yi; Waterhouse, Geoffrey I. N.; Lu, Siyu
Abstract: Carbon dots (CDs) possess outstanding luminescence properties, making them widely used in optical displays, anti‐counterfeiting systems, bioimaging, and sensors. Presently, there is much debate about the classification of CDs, as well as their formation process, structure, and fluorescence mechanisms. Aggregation plays an important role in the formation and fluorescence (e.g., aggregation‐induced emission) of CDs, yet is seldom studied in detail. This review aims fill this knowledge gap, by first exploring how aggregation leads to the formation of different types of CDs (e.g., graphene quantum dots, carbon quantum dots, and carbonized polymer dots), followed by a detailed examination of the effect of aggregation‐induced morphology on the luminescence properties and application of CDs. Finally, opportunities and challenges for the application of CDs in various applications are discussed, with the need for better mechanistic understanding of aggregation‐induced luminescence being an imperative. Abstract : Carbon dots (CDs) has excellent photoluminescence properties. Aggregation plays an important role in both the formation of CDs and their fluorescence, yet is seldom studied in detail. This review aims to fill this knowledge gap. We first discuss how aggregation leads to the formation of different types of CDs, and the impact on morphology, luminescence, and applications.